The global economic burden of health anxiety/hypochondriasis - a systematic review - Kawka, Hannah; Kurtz, Marie; Horstick, Olaf; Brenner, Stephan; Deckert, Andreas; Lowery, Wilson Michael; Bärnighausen, Till; Dambach, Peter (BMC public health, 2023)
Background: Recent studies have shown a lifetime prevalence of 5.7% for health anxiety/hypochondriasis resulting in increased healthcare service utilisation and disability as consequences. To the best of our knowledge, there has been no systematic review examining the global costs of hypochondriasis, encompassing both direct and indirect costs. Our objective was to synthesize the available evidence on the economic burden of health anxiety and hypochondriasis to identify research gaps and provide guidance and insights for policymakers and future research. Methods: A systematic literature search was conducted using PubMed, Web of Science, PsycInfo, EconLit, IBSS and Google Scholar without any time limit, up until April 2022. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in this search and the following article selection process. The included studies were systematically analysed and summarized using a predefined data extraction sheet. Results: Of the 3044 articles identified; 10 publications met our inclusion criteria. The results displayed significant variance in the overall costs listed among the studies. The reported economic burden of hypochondriasis ranged from 857.19 to 21137.55 US$ per capita per year. Most of the investigated costs were direct costs, whereas the assessment of indirect costs was strongly underrepresented. Conclusion: This systematic review suggests that existing studies underestimate the costs of hypochondriasis due to missing information on indirect costs. Furthermore, there is no uniform data collection of the costs and definition of the disease, so that the few existing data are not comparable and difficult to evaluate. There is a need for standardised data collection and definition of hypochondriasis in future studies to identify major cost drivers as potential target point for interventions.
Gesehen am 20.02.2024